2020
DOI: 10.1111/aogs.13928
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression levels among pregnant women with COVID‐19

Abstract: nant women during the COVID-19 pandemic 1 as maternal mental health can be associated with short-and long-term risks for their and their children's physical and psychological health. Most studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 5 publications
5
82
1
12
Order By: Relevance
“…Such results were expected in light of both the severity of the crisis caused by the pandemic, and the psychological vulnerability of pregnant women in general. They are also in line with the findings of other authors who identified higher levels of stress in pregnant women across the world (Berthelot et al, 2020, Corbett et al, 2020, Durankuş & Aksu, 2020, Kotabagi et al, 2020, Lebel et al, 2020, Masjoudi et al, 2020, Nanjundaswamy et al, 2020, Saadati et al, 2020, Saccone et al, 2020. Our study suggests that the intensity of fear of COVID-19 directly affects the stress response, but that there are also several psychological factors modulating this relationship.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such results were expected in light of both the severity of the crisis caused by the pandemic, and the psychological vulnerability of pregnant women in general. They are also in line with the findings of other authors who identified higher levels of stress in pregnant women across the world (Berthelot et al, 2020, Corbett et al, 2020, Durankuş & Aksu, 2020, Kotabagi et al, 2020, Lebel et al, 2020, Masjoudi et al, 2020, Nanjundaswamy et al, 2020, Saadati et al, 2020, Saccone et al, 2020. Our study suggests that the intensity of fear of COVID-19 directly affects the stress response, but that there are also several psychological factors modulating this relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Several empirical studies and preliminary reports dealing with the psychological consequences of the pandemic on pregnant women have been published (Berthelot et al, 2020, Corbett et al, 2020, Durankuş & Aksu, 2020, Kotabagi et al, 2020, Lebel et al, 2020, Masjoudi et al, 2020, Milne et al, 2020, Nanjundaswamy et al, 2020, Saadati et al, 2020, Saccone et al, 2020, all pointing to the same conclusion that pregnant women experience significantly higher levels of stress and anxiety during the pandemic. The perceived levels of distress and psychiatric symptoms among pregnant women in Quebec were higher than before the pandemic, after controlling for age, gestational age, household income, education, and lifetime psychiatric disorders (Berthelot, 2020).…”
mentioning
confidence: 99%
“…These studies have reported an increase in symptoms of depression ( Dong et al, 2020 ; Durankuş & Aksu, 2020 ; Sun et al, 2020) and anxiety ( Kotabagi et al, 2020 ; Liu et al, 2020 ), lower quality of mental life (Kwasi Ahorsu et al, 2020), increase in perceived levels of distress ( Berthelot et al, 2020 ) and moderate psychological impact due to isolation (Saccone et al, 2020). In addition, other studies have identified that psychopathological indicators increase with the number of confirmed COVID-19 cases or daily deaths ( Zhou et al, 2020 ), and that both anxiety and depression symptoms decrease when isolation measures are suspended ( Kotagabi et al, 2020 ). However, there is no record of studies that have longitudinally monitored this population throughout the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…43 Additionally, based on a small case series, Kotabagi et al proposed a positive correlation between both clinically relevant maternal anxiety and depression and the number of COVID-19-related deaths in the population. 48 The unpredictability of COVID-19, along with deprivation of social and family support, increased perinatal distress. 49 A global survey of pregnant and postpartum women by Koenen and colleagues found that 40% of women screened positive for post-traumatic stress disorder (PTSD); over 70% of women also reported clinically signi cant depression or anxiety.…”
Section: Mental Healthmentioning
confidence: 99%